Celebrating Polyoxometalate Chemistry. Issue 3 (24th January 2019) - Pope, Michael T.; Sadakane, Masahiro; Kortz, Ulrich
Abstract : Michael Pope, Masahiro Sadakane, and Ulrich Kortz present a short history of polyoxometalates, listing important anniversaries.